Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a/ ĐKXĐ:...
\(\Leftrightarrow4x^2-4x\sqrt{2x-1}-3x^2+6x-3=0\)
\(\Leftrightarrow4x\left(x-\sqrt{2x-1}\right)-3\left(x-1\right)^2=0\)
\(\Leftrightarrow\frac{4x\left(x-1\right)^2}{x+\sqrt{2x-1}}-3\left(x-1\right)^2=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=1\\\frac{4x}{x+\sqrt{2x-1}}=3\left(1\right)\end{matrix}\right.\)
\(\left(1\right)\Leftrightarrow4x=3x+3\sqrt{2x-1}\)
\(\Leftrightarrow x=3\sqrt{2x-1}\)
\(\Leftrightarrow x^2-18x+9=0\) \(\Rightarrow9\pm6\sqrt{2}\)
Vậy pt có 3 nghiệm....
b/ ĐKXĐ:...
\(\Leftrightarrow4x^2-4x\sqrt{4x-3}-x^2+4x-3=0\)
\(\Leftrightarrow4x\left(x-\sqrt{4x-3}\right)-\left(x^2-4x+3\right)=0\)
\(\Leftrightarrow\frac{4x\left(x^2-4x+3\right)}{x+\sqrt{4x-3}}-\left(x^2-4x+3\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x^2-4x+3=0\Rightarrow x=...\\\frac{4x}{x+\sqrt{4x-3}}=1\left(1\right)\end{matrix}\right.\)
\(\left(1\right)\Leftrightarrow4x=x+\sqrt{4x-3}\)
\(\Leftrightarrow3x=\sqrt{4x-3}\)
\(\Leftrightarrow9x^2-4x+3=0\) (vô nghiệm)
Vậy...
pt <=> x2 - 4x + 21 - 6\(\sqrt{2x+3}\) = 0
<=> (x2 - 6x + 9) + [(2x + 3) - 6\(\sqrt{2x+3}\) + 9]
<=> (x - 3)2 + (\(\sqrt{2x+3}\) - 3)2 = 0
<=> \(\left\{{}\begin{matrix}x-3=0\\\sqrt{2x+3}-3=0\end{matrix}\right.\)
<=> \(\left\{{}\begin{matrix}x=3\\2x+3=9\end{matrix}\right.\)
<=> \(\left\{{}\begin{matrix}x=3\\x=3\end{matrix}\right.\)
Vậy x = 3
ĐK : \(x\ge-\frac{3}{2}\)
\(PT\Leftrightarrow x^2-4x+21-6\sqrt{2x+3}=0\)
\(\Leftrightarrow\left(2x+3-6\sqrt{2x+3}+9\right)+\left(x^2-6x+9\right)=0\)
\(\Leftrightarrow\left(\sqrt{2x+3}-3\right)^2+\left(x-3\right)^2=0\)
\(\Leftrightarrow\hept{\begin{cases}\sqrt{2x+3}-3=0\\x-3=0\end{cases}\Leftrightarrow\hept{\begin{cases}2x+3=9\\x=3\end{cases}\Rightarrow}x=3\left(TM\right)}\)
Vậy nghiệm của PT là \(x=3\)